Lithuanian dabar̃ ‘now’ and the Baltic *-ā́-illative - Ostrowski, Norbert (Vilnius University Open Series, 2022)
Lithuanian dabar̃ ‘now’ comes from the illative of the continuative adverb dãbar ‘still, yet’; schematically: dãbar ‘still, yet’ → illative *dabar-ā́ > *dabarà > dabar̃ ‘now’. Change in accentuation visible in dãbar ‘still, yet’ vs. dabar̃  ‘now’ brings to mind a similar process in illative forms, e.g. acc.sg. *mìškan → ill.sg. *miškan-ā́ > dial. miškanà > ill.sg. miškañ. The primary illative *dabar- ā́ is preserved in the dialectal dabarõs ‘now’, which is traced back to a contraction of *dabar-à-es. The postposition *-es is a mark of the enclitic verb esti ‘is’. The shift of accent like between dãbar ‘still, yet’ and dial. dabarõs ‘now’ can also be observed in a few other adverbs, e.g. *pa gãli (cf. OLith. ik’ gâli ‘to the end’) → pagaliõs ‘in the end’.
Keywords: Baltic; postpositions; illative; etymology; enclitics